(untitled) (Global Scientific Review, 2024)
The article talks about the Sitorai Mokhi Khosa palace-garden of Bukhara, built at the end of the 19th century and the beginning of the 20th century. It also discussed the architectural compositional solution of the palace, traditional artistic decorations, modern and national architectural styles and elements. The creative works of the architects and masters who participated in its construction are also discussed.